Effect of Chemo- and Immunotherapy of Hemoblastosis on The Endocrine System - Tatevik Melkumyan (Scientific Trends, 2025)
Chemo- and immunotherapy of hemoblastoses, including leukemia, lymphoma and myeloma, are associated with the development of a wide range of acute and delayed endocrinopathies. The pathogenesis of these conditions is multifactorial and includes direct cytotoxic action, autoimmune activation, systemic inflammation and secondary effects of transplantation. The article summarizes data on the frequency, pathogenesis and clinical manifestations of endocrinopathies in oncohematological patients. Practical recommendations for their screening and monitoring, as well as on issues of fertility preservation are presented.
Keywords: Hemoblastoses, chemotherapy, immunotherapy, checkpoint inhibitors, CAR-T therapy, hematopoietic stem cell transplantation, endocrine complications, hypothyroidism, hypophysitis, autoimmune diabetes, gonadal insufficiency.